Systematic interlinking of school, transition system and training : an interview with Peter Thiele on the BMBF initiative "Chains of educational progression through to initial vocational qualification" - Thiele, Peter [Interviewter]; Jäger, Christiane [Interviewer] (My University, 2011)
"The vocational education and training system has undergone considerable change during the past 20 years. Large numbers of vocational preparation schemes or programmes leading to partial vocational qualification have grown up alongside the dual system of vocational education and training, but these only provide some of the young people concerned with successful transitions into vocational training leading to a recognised qualification. Over the course of recent years, numerous programmes and initiatives have been introduced at an individual, regional and structural level in an attempt to increase the efficiency of the transition system. September 2010 brought the launch of the BMBF Initiative 'Chains of educational progression through to initial vocational qualification.'" (BIBB)
Keywords: G 1.3.2.2 Übergänge; P 1.7 Benachteiligte; S 2.3.2 Programme in der Berufsbildung; S 3.5.1.1 Bundesministerium für Bildung und Forschung (BMBF); Übergangssystem; Effizienz; Benachteiligtenförderung; Förderprogramm; Berufsorientierung; Berufsvorbereitung; Bildungsbegleitung